Between Coexistence and Cooperation: Education for Sustainable Development at Universities and Establishments of Environmental Education - Hemmer, Ingrid; Bagoly-Simó, Péter; Fischer, Caroline (Journal of Geography Education, 2013)
One way to improve Education for Sustainable Development (ESD) is to link formal with non-formal education. Therefore, this empirical study takes a closer look at the quality and quantity of cooperation between institutions of higher education and establishments of Environmental Education (EE). All approved Bavarian EE establishments were asked to deliver information about their cooperation with universities in the areas of teaching, research, and educational offer. In order to describe basic patterns, network theories and research methods were used. The results show weak intensity and continuity of networking. While universities and establishments of EE cooperate frequently in the area of teaching, other areas show much weaker interconnectedness. Furthermore, establishments of EE are explicitly seeking cooperation with universities in the area of evaluation.